Developing Android-Based Chemistry Learning Media Using the Inquiry Model to Improve Students’ Learning Outcomes and Critical Thinking Ability - Afrina, Meydia; Siska, Jumiati; Danim, Sudarwan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Students’ critical thinking and their ability to learn outcomes depend on the learning design and student activities. Most of the students use their free time by playing gadgets. Students learn faster with the features contained in gadgets than learning from sources in the form of textbooks. This phenomenon is the background for researchers to develop android-based chemical media which has several menus that can be explored by students in learning. Android-based chemical media was developed using the Smart Apps Creator application. This study aims to develop a digital media that is compatible with the android system. In this study the media is used to improve cognitive learning and critical thinking. In addition, it also aims to evaluate the responses of students in learning chemistry through the topic of Oxidation Reduction Reactions. The development of this media was adapted from the procedure of the interactive mobile learning development process. The collection of evaluation data models that are applied are pre-test and post-test in the test class. Based on the results of the development carried out, it can be concluded that the developed android-based chemical media has met the appropriate criteria. This media can help educators in the learning process effectively and optimally and make students interested in learning chemistry.